Atomistic calculation of the f0 attempt frequency in Fe3O4 magnetite nanoparticles - Moreno, Roberto; Jenkins, Sarah; Williams, Wyn; Evans, Richard F. L. (2024)
Fil: Moreno, Roberto. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto de Física Enrique Gaviola; Argentina.